A Transcriptomic Model of Postnatal Cardiac Effects of Prenatal Maternal Cortisol Excess in Sheep - Antolic, Andrew; Richards, Elaine M.; Wood, Charles E.; Keller-Wood, Maureen (Frontiers in Physiology, 2019)
In utero treatment with glucocorticoids have been suggested to reprogram postnatal cardiovascular function and stress responsiveness. However, little is known about the effects of prenatal exposure to the natural corticosteroid, cortisol, on postnatal cardiovascular system or metabolism. We have demonstrated an increased incidence of stillbirth in sheep pregnancies in which there is mild maternal hypercortisolemia caused by infusion of 1 mg/kg/d cortisol. In order to model corticosteroid effects in the neonate, we created a second model in which cortisol was infused for 12 h per day for a daily infusion of 0.5 mg/kg/d. In this model we had previously found that neonatal plasma glucose was increased and plasma insulin was decreased compared to those in the control group, and that neonatal ponderal index and kidney weight were reduced and left ventricular wall thickness was increased in the 2 week old lamb. In this study, we have used transcriptomic modeling to better understand the programming effect of this maternal hypercortisolemia in these hearts. This is a time when both terminal differentiation and a shift in the metabolism of the heart from carbohydrates to lipid oxidation are thought to be complete. The transcriptomic model indicates suppression of genes in pathways for fatty acid and ketone production and upregulation of genes in pathways for angiogenesis in the epicardial adipose fat (EAT). The transcriptomic model indicates that RNA related pathways are overrepresented by downregulated genes, but ubiquitin-mediated proteolysis and protein targeting to the mitochondria are overrepresented by upregulated genes in the intraventricular septum (IVS) and left ventricle (LV). In IVS the AMPK pathway and adipocytokine signaling pathways were also modeled based on overrepresentation by downregulated genes. Peroxisomal activity is modeled as increased in EAT, but decreased in LV and IVS. Our results suggest that pathways for lipids as well as cell proliferation and cardiac remodeling have altered activity postnatally after the in utero cortisol exposure. Together, this model is consistent with the observed increase in cardiac wall thickness at necropsy and altered glucose metabolism observed in vivo, and predicts that in utero exposure to excess maternal cortisol will cause postnatal cardiac hypertrophy and altered responses to oxidative stress.